The Effect of Training on the Utilization of Herbal Plants and Entrepreneurial Motivation Towards Improving Community Economic Welfare - Dyah Pikanthi Diwanti; Nurani Indah Pertiwi (Fakultas Ekonomi, Universitas Negeri Jakarta, Indonesia, 2022)
At this time, a healthy environment is everyone's dream. A healthy environment is strongly influenced by the accompanying conditions, one of which is the awareness of protecting nature with the availability of medicinal plants/herbs that can be healthy consumption for the community. Banyumas Regency is one area that has the potential to utilize herbal plants supported by environmental conditions that have fertile natural potential. This study aims to determine the effect of training on the use of herbal plants and entrepreneurial motivation on improving the economic welfare of the community. This study used a quantitative method with Nasyiatul 'Aisyiyah Regional Leadership in Banyumas Regency as the respondent. The results showed that training on the use of herbal plants had a 62.2% greater influence than 37.8% entrepreneurial motivation on the community's economic welfare. Keywords: Training, Herbal Plants, Entrepreneurial Motivation, Economic Welfare